Strategic Management of Public Transport Accessibility in Realising Semarang as a Green City - Putra Endra Kurniawan; Atmojo Muhammad Eko; Rassanjani Saddam (E3S Web of Conferences)
The increase in private vehicles every year has led the Semarang City Government to design a public transport called Trans Semarang. In 2009, Trans Semarang began operating and until now there have been 8 corridors and 4 feeders spread across Semarang City. The research method used is descriptive qualitative research. The research used 5 indicators: strategy formulation, strategy implementation, strategy evaluation, location-based accessibility, and institutional system. The result of this research shows that the accessibility improvement strategy consists of cooperation with ITDP, GIZ, Bappeda, and Transjakarta. The cooperation carried out is to build sustainable transport planning and dedicated line development. In addition, the use of CNG to reduce exhaust emissions in the Trans Semarang fleet. Then, there is the use of technology such as the creation of the Trans Semarang application. On the other hand, there is an evaluation conducted by BLU UPTD Trans Semarang to control the operation both internally and externally. The development of the institutional system also has a big influence on the development of human resources, such as the special requirements and special training conducted by Trans Semarang members.